A systematic literatur review of remuneration non-wage and OCB - Pramita, Cindy (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2022)
This systematic literature review aims to summarize some a study of remunation non-wage and the effects of his OCB. Methodology/Approach - This study preferred report items for literature search methods. systematic review and meta-analysis (PRISMA), From a study on the impact remuneration of non-wage on OCB in other words Google Scholar. 198 records total filter using data inclusion criteria to get 30 data those who meet the certification criteria. Result - Finding 45 hypotheses related to remuneration non-wage and OCB. Based on impact and functional data these variables are grouped into four. That is, it has positive significance. Influential variables, unaffected variables, mediator variables. Novelty/Value - Different studies related to different types of fringe benefits should be categorized against OCB in the last 5 years from 2017 to 2022. Dates are used in this systematic literature review from journals indexed by Scopus. Result - A systematic literature review found that providing non-remuneration, in addition to base salary, can affect organizational citizenship behavior from a job. because Employees can do more than just volunteer so they see value in non-wage remuneration can minimize work stress as well as increase work motivation. It can be concluded that non-wage labor costs can affect an organization's civic behavior.